Nymphanthus namkadingensis, a new species of Phyllanthaceae from Laos - Yamamoto, Takenori; Souladeth, Phetlasy; Phonepaseuth, Phongphayboun; Kongxaisavath, Deuanta; Vongthavone, Thyraphon; Ba Vuong, Truong; Quoc Trong, Pham; Souvannakhoummane, Keooudone; Tagane, Shuichiro (Phytotaxa, 2024)
A new species of Nymphanthus (Phyllanthaceae), N. namkadingensis from Bolikhamxai Province, central Laos, is described and illustrated, along with its vernacular name and preliminary conservation status. The new species is similar to N. rubescens, but distinguished by having larger stipules, longer pedicels, and connate annular disc glands (vs. free disc glands) of pistillate flowers.